Persepsi mahasiswa akuntansi terhadap perilaku pengungkapan kecurangan akademik di Bandar Lampung - sari, Natalia Catur Wulan; Dwi Septiana, Theodora; Sinaga, Imelda; Ari Palma Akadiati, Victoria (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
Abstract The purpose of this study is to re-examine the perceptions of accounting students in disclosing academic fraud in Bandar Lampung so that students dare to become whistleblowers who reveal academic fraud on campus internally and for lecturers it is useful to improve teaching methods and the application of learning in the curriculum, especially accounting in educating students as candidates. Qualified accountants or auditor candidates in the future. For universities, this research is useful as an evaluation material in processing GCG (Good Corporate Governance). The method used in this study is a descriptive method using qualitative data. Research result obtained in this study are the influence of attitudes on behavior in disclosing fraud (whistleblowing) in Bandar Lampung does not have a significant effect, perceptions of subjective norms in disclosing fraud (whistleblowing) in Bandar Lampung have no significant effect, perceptions of behavioral control in disclosing fraud (whistleblowing) in Bandar Lampung has a significant effect, and the level of seriousness of fraud in the disclosure of fraud (whistleblowing) in Bandar Lampung has no significant effect.